Animal models of medullary thyroid cancer: state of the art and view to the future. Issue 1 (January 2017) - Vitale, Giovanni; Gaudenzi, Germano; Circelli, Luisa; Manzoni, Marco F; Bassi, Andrea; Fioritti, Niccolò; Faggiano, Antongiulio; Colao, Annamaria; ,
Abstract : Medullary thyroid carcinoma is a neuroendocrine tumour originating from parafollicular C cells accounting for 5–10% of thyroid cancers. Increased understanding of disease-specific molecular targets of therapy has led to the regulatory approval of two drugs (vandetanib and cabozantinib) for the treatment of medullary thyroid carcinoma. These drugs increase progression-free survival; however, they are often poorly tolerated and most treatment responses are transient. Animal models are indispensable tools for investigating the pathogenesis, mechanisms for tumour invasion and metastasis and new therapeutic approaches for cancer. Unfortunately, only few models are available for medullary thyroid carcinoma. This review provides an overview of the state of the art of animal models in medullary thyroid carcinoma and highlights future developments in this field, with the aim of addressing salient features and clinical relevance.